Umbrella clauses and autonomy regulation: assessing the impact on indonesia's regulatory capability for the public interest - Nindyatsyah (Trigin Publisher, 2023)
Foreign Direct Investment (FDI) plays a key role in the contemporary global economy. The Bilateral Investment Treaty (BITs) guarantees equitable treatment in Investment Arbitration and Contractual Commitments, despite the divergent goals of the home and host countries involved. The emergence of certain events gave rise to a conflict resolution issue, which subsequently led to the implementation of an umbrella clause aimed at safeguarding investments associated with contract violations. The